Smart Reusable Airbag System for Fall Detection and Protection - J Jasonraj; K Karthikeyan; M Nandhini; R Sahana; E Vignesh (International Journal of Scientific Research in Science and Technology, 2025)
This project introduces an intelligent, wearable airbag system designed to enhance safety for two primary user groups: elderly individuals and riders of two-wheeled vehicles. Falls represent one of the most serious health risks for older adults, while motorcycle crashes continue to account for a large proportion of trauma incidents. The proposed system integrates real-time motion tracking with an automated protection mechanism to reduce the severity of impact injuries. An MPU6050 sensor continuously measures acceleration, angular velocity, and posture. When the system detects a fall or sudden imbalance, it transmits data to an Arduino - based controller, which triggers a compact DC air pump. The pump inflates an air bladder using ambient air, and the air is then directed through a solenoid valve into a TPU airbag strategically positioned around critical body areas such as the chest, back, and hips. Inflation occurs within milliseconds, creating a cushion that mitigates impact forces. In contrast to single-use CO₂ cartridge airbags, this design is reusable, lightweight, and cost-efficient, making it suitable for daily wear. Integrated into vests or jackets and powered by a rechargeable battery, the system operates autonomously, offering a practical and affordable safety solution for seniors, motorcyclists, patients in rehabilitation, and others at risk of falls.
Keywords: Fall Prevention; Smart Wearable Airbag; Elderly Protection; Motion Tracking; MPU6050 Sensor; Arduino Controller; DC Air Pump; TPU Inflatable Cushion; Reusable Safety Device